Combinatorial synthesis of Cr1 − xAlxN and Ta1 − xAlxN coatings using industrial scale co-sputtering. (2nd April 2016) - Schalk, N.; Weirather, T.; Sabitzer, C.; Hirn, S.; Terziyska, V. L.; Gangopadhyay, S.; Czettl, C.; Polcik, P.; Kathrein, M.; Mitterer, C.
Abstract : For a comprehensive understanding of the scientific relations between composition, microstructure and properties of hard coatings usually a multitude of deposition runs is necessary. Within the present work, a combinatorial deposition approach using triangular shaped segmented sputter targets was adapted for an industrial scale sputter system. Owing to the position of the substrates relative to the target segments, a wide range of compositions can be achieved within a single deposition run. To verify this concept, Cr1 − x Alx N reference coatings and Ta1 − x Alx N coatings, each with a base layer of TiAlN (i.e. a bilayer configuration), were synthesised. The effect of the varying chemical compositions on the structure and mechanical as well as tribological properties was investigated. This approach enables to efficiently identify promising coating compositions.